Insulating anticorrosive and anti-condensation coating and preparation method thereof
By combining modified resins and hydrophobic additives, an insulating, anti-corrosion, and anti-condensation coating with strong hydrophobicity and high chemical inertness was prepared. This solved the problems of corrosion and condensation prevention of existing coatings in complex environments, and achieved the coating's high-efficiency insulation and easy-to-clean properties.
Patent Information
- Application Number
- CN202511886656.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-12-15
AI Technical Summary
Existing insulation materials are insufficient in terms of corrosion resistance and anti-condensation performance. In particular, they are prone to coating peeling and water film formation in complex environments, leading to insulation failure. Moreover, existing coating processes are complex and costly, making it difficult to simultaneously meet the synergistic requirements of insulation, corrosion resistance, and anti-condensation.
An insulating, anti-corrosion, and anti-condensation coating is prepared by combining modified resin and hydrophobic additives through a specific synthesis method. The modified resin contains fluorinated side chains to form a strongly hydrophobic surface, while the hydrophobic additives form a superhydrophobic surface, enhancing the anti-condensation and anti-corrosion properties. Dispersants, defoamers, and leveling agents are added to improve the uniformity and adhesion of the coating.
Significantly improves the anti-condensation, anti-corrosion, and anti-fouling properties of coatings. The use of modified resins and hydrophobic additives makes the coating surface highly hydrophobic, preventing water film formation, blocking corrosive media, enhancing insulation reliability and ease of cleaning, reducing surface energy to promote water droplet roll-off, and improving protective capabilities.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrical insulation materials technology, specifically relating to an insulating, anti-corrosion, and anti-condensation coating and its preparation method. Background Technology
[0002] In the field of power equipment protection, existing insulation materials have significant shortcomings in corrosion resistance and condensation prevention. Traditional power insulation materials such as cross-linked polyethylene and silicone rubber, while possessing basic insulation functions, rely on external coatings for corrosion resistance, making them ill-suited for complex environments such as salt spray and chemical corrosion. This is particularly true in scenarios like offshore platforms and chemical facilities, where coating peeling can easily lead to insulation failure. Regarding condensation prevention, conventional solutions such as heating dehumidification and room-temperature vulcanizing silicone rubber coatings have limitations: heating devices consume high energy and may exacerbate local temperature differences; room-temperature vulcanizing coatings exhibit reduced hydrophobicity in high-humidity environments, easily forming water films and triggering flashover. Furthermore, the use of multiple materials leads to complex processes and increased costs, while single-function coatings cannot simultaneously meet the synergistic requirements of insulation, corrosion resistance, and condensation prevention. Therefore, there is an urgent need to develop composite coatings that combine all three protective functions to improve equipment operating safety and economy.
[0003] Patent CN118165592B discloses a nano-anti-condensation transparent insulating coating suitable for power grids and its preparation method, comprising the following raw materials in parts by weight: 30-50 parts acrylic resin, 10-20 parts polyamide resin, 5-10 parts nano-silica, 2-5 parts nano-titanium dioxide, 5-10 parts barium sulfate, 2-3 parts dispersant, 1-2 parts defoamer, and 1-2 parts leveling agent. This invention also discloses a method for preparing the nano-insulating coating, which involves modifying and pre-mixing the nanoparticles, then mixing them with resin materials and additives to ensure effective dispersion of the raw materials. Compared to existing technologies, the nano-insulating coating obtained by this invention not only possesses the characteristics of existing insulating coatings but also exhibits thin film thickness, good insulation performance, superior hydrophobicity, significant anti-condensation effect, and strong self-cleaning and environmentally friendly properties. Although the nano-anti-condensation transparent insulating coating prepared according to the above patent demonstrates excellent performance in insulation, hydrophobicity, and self-cleaning, there is still room for improvement in its anti-condensation and anti-corrosion effects. This is mainly because although nano-silica and nano-titanium dioxide can enhance hydrophobicity, the uniformity of particle dispersion is limited by the process, and local agglomeration may form micropores, leading to water vapor penetration. At the same time, fillers such as barium sulfate have limited barrier capabilities against corrosive media. In strong acid, alkali or high salt spray environments, the density of the coating decreases after long-term use, which in turn affects the durability of anti-condensation and anti-corrosion performance. Further optimization of nanoparticle modification and composite processes is needed. Summary of the Invention
[0004] The purpose of this invention is to provide an insulating, anti-corrosion, and anti-condensation coating and its preparation method, which solves the technical problems of poor anti-corrosion effect, anti-condensation effect, and self-cleaning effect of coatings in the prior art.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] This invention provides an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 25-32 parts epoxy resin, 18-26 parts modified resin, 20-28 parts distilled water, 6-14 parts hydrophobic additive, 12-20 parts filler, 1-3 parts dispersant, 1-2 parts defoamer, and 1-2 parts leveling agent.
[0007] Preferably, the method for preparing the modified resin includes the following steps:
[0008] Q1: Decamethylcyclopentasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred, and then trifluoromethanesulfonic acid was added. The mixture was heated under a nitrogen atmosphere. After the reaction was completed, hexamethyldisilazane was added, magnetically stirred, dried, stirred, filtered, and distilled under reduced pressure to obtain liquid 1.
[0009] Q2: Perfluorohexyl ethyl acrylate and platinum catalyst were added to a container containing toluene. Under a nitrogen atmosphere, the mixture was stirred. Then, liquid 1 was mixed with toluene and added to the container. The mixture was heated to react. After the reaction was completed, ionone dissolved in toluene was added and the mixture was stirred to continue the reaction. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0010] The synthesis reaction formula for the modified resin in the above process is as follows:
[0011]
[0012] Preferably, in Q1, the ratio of decamethylcyclopentasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, 1,1,3,3-tetramethyldisiloxane, trifluoromethanesulfonic acid, and hexamethyldisilazane is (2.2-2.7) g : (18.1-18.9) g : (0.21-0.33) g : (0.004-0.006) mL : (0.021-0.025) g. The mixture is magnetically stirred for 20-30 min, heated to a reaction temperature of 50-55 °C, and the reaction time is 48-52 h. After magnetic stirring for 2-4 h, the mixture is dried with anhydrous sodium sulfate and stirred for 4-6 h.
[0013] Preferably, in Q2, the ratio of perfluorohexyl ethyl acrylate, platinum catalyst, liquid 1, and ionone is (3.12-3.88) g : (0.005-0.008) mL : (9.22-10.68) g : (7.12-7.78) g, stirred for 1-2 h, heated to 98-102℃ for 20-26 h, and stirred for another 20-24 h.
[0014] Preferably, the method for preparing the hydrophobic additive includes the following steps:
[0015] S1: Add ethyl diazonium acetate to a container containing dichloromethane. Under ice bath conditions, add pyridine, stir magnetically, and then add dichloromethane containing heptafluorobutyric anhydride. After the addition is complete, react at room temperature, add distilled water, and then add saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a.
[0016] S2: Under a nitrogen atmosphere, copper hydroxide, 4-bromoacetophenone, organic compound a and Tempo were added sequentially to a container containing tetrahydrofuran, followed by the addition of DBU. After sealing the reaction, organic compound b was obtained.
[0017] S3: Add organic compound b to a container containing sodium hydroxide aqueous solution, react in an oil bath, add sulfuric acid aqueous solution, adjust the pH, filter, reflux, rotary evaporate, and vacuum dry to obtain organic compound c;
[0018] S4: Add organic compound c to a container containing toluene, stir, add dodecanol, then add p-toluenesulfonic acid, heat in an oil bath to react, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0019] The synthesis reaction formula for the hydrophobic additive in the above process is as follows:
[0020]
[0021] The mass spectrometry analysis results for organic compound a were: m / z: 310.02 (100.0%), 311.02 (9.5%); for organic compound b, m / z: 489.98 (100.0%), 491.97 (97.3%), 490.98 (17.5%), 492.98 (17.2%), 491.98 (2.2%), 493.98 (2.0%); and for organic compound c, m / z: 461.95 (100.0%), 463.94 (97.3%), 462.95 (15.3%), 464.95 (15.0%), 463.95 (1.8%), 465.95. (1.7%); The mass spectrometry analysis results of the hydrophobic additives were as follows: m / z: 630.13 (100.0%), 632.13 (97.5%), 631.14 (28.6%), 633.13 (28.2%), 632.14 (4.6%), 634.14 (4.5%).
[0022] Preferably, in S1, the ratio of ethyl diazoate, pyridine, heptafluorobutyric anhydride and distilled water is (5.5-6.8) mL : (5.1-5.8) mL : (26.88-27.54) g : (30-45) mL, the ice bath temperature is 0-1℃, the magnetic stirring is performed for 10-20 min, and the reaction is carried out at room temperature for 8-10 h.
[0023] Preferably, in S2, the ratio of copper hydroxide, 4-bromoacetophenone, organic compound a, Tempo, tetrahydrofuran, and DBU is (0.18-0.23) mg: (35-45) mg: (123-129) mg: (92.2-96.5) mg: (1-2) mL: (91.5-93.8) mg, the sealed reaction temperature is 20-25℃, and the time is 4-6 h.
[0024] Preferably, in step S3, the ratio of organic matter b to sodium hydroxide aqueous solution is (72.6-84.3) mg: (4.5-5.5) mL, the mass fraction of sodium hydroxide aqueous solution is 10 wt%, the volume fraction of sulfuric acid aqueous solution is 20 wt%, the pH is adjusted to 3-3.2, and the solution is refluxed in 37% hydrochloric acid solution for 30-45 min.
[0025] Preferably, in S4, the ratio of organic compound c, toluene, dodecyl alcohol and p-toluenesulfonic acid is (3.42-4.18) g : (12.2-16.8) mL : (3.56-4.54) g : (0.22-0.28) g, the oil bath heating reaction temperature is 110-130℃, and the time is 8-10 h.
[0026] Preferably, the method for preparing the insulating, anti-corrosion, and anti-condensation coating includes the following steps:
[0027] Step 1: Add the dispersant to a container filled with distilled water, stir, then add epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0028] Step 2: Add the filler and hydrophobic additive to the mixed base material in sequence, mix evenly, grind, add defoamer and leveling agent, stir and mix, filter, and mature to obtain an insulating, anti-corrosion and anti-condensation coating.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] 1. This invention first uses decamethylcyclopentasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, 1,1,3,3-tetramethyldisiloxane, hexamethyldisilazane, perfluorohexylethyl acrylate, and ionone as raw materials to prepare a modified resin. Subsequently, using ethyl diazo, heptafluorobutyric anhydride, 4-bromoacetophenone, and dodecanol as raw materials, a hydrophobic additive is prepared. Adding the obtained modified resin and hydrophobic additive to the coating preparation process can effectively improve its anti-condensation, anti-corrosion, and anti-flashover properties, while also enhancing the coating's insulation reliability and adhesion performance.
[0031] 2. The modified resin obtained in this invention is added to the coating, which can effectively improve its anti-condensation performance, stain resistance, and corrosion resistance. The fluorinated side chains contained in the modified resin can significantly reduce the surface energy of the coating, increase the contact angle of water on its surface, form a strongly hydrophobic surface, effectively prevent the formation of water film, and promote the condensation of water molecules to roll off in the form of small water droplets, greatly alleviating the condensation problem. At the same time, the low surface energy also gives the coating excellent anti-fouling and easy-to-clean properties. Moreover, the superhydrophobic surface directly blocks the contact between corrosive media and the substrate. The organosilicon and fluoropolymer have a dense structure and high chemical inertness, which can effectively resist the erosion of media such as acids, alkalis, and salts, and improve its physical shielding and chemical protection performance.
[0032] 3. This invention adds the prepared hydrophobic additive to the coating, which can effectively improve its anti-condensation performance, anti-corrosion performance, and anti-flashover performance. The superhydrophobic surface formed by the hydrophobic additive greatly reduces the actual contact area between water droplets and the coating. The condensed water droplets are spherical due to surface tension and quickly roll off under gravity or slight wind, unable to adhere and form a water film. At the same time, the dense hydrophobic coating itself isolates water, oxygen, and corrosive ions, improving the coating's protective ability and delaying corrosion. The superhydrophobic surface is difficult to wet with water, sewage cannot form a continuous conductive film, and it also has a repellent effect on pollutants such as grease. The rolling water droplets can carry away most of the surface dirt, keeping the insulator clean. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] Example 1: This example discloses a method for preparing a modified resin, including the following steps:
[0035] Q1: 2.45 g of decamethylcyclopentasiloxane, 18.5 g of 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 0.27 g of 1,1,3,3-tetramethyldisiloxane were added to a container and magnetically stirred for 20 min. Then, 0.005 mL of trifluoromethanesulfonic acid was added. The mixture was heated at 50 °C for 48 h under a nitrogen atmosphere. After the reaction was completed, 0.023 g of hexamethyldisilazane was added and magnetically stirred for 3 h. The mixture was then dried with anhydrous sodium sulfate and stirred for 6 h. After filtration and vacuum distillation, liquid 1 was obtained.
[0036] Q2: 3.51g of perfluorohexyl ethyl acrylate and 0.006mL of platinum catalyst were added to a container containing 20mL of toluene. The mixture was stirred for 2h under a nitrogen atmosphere. Then, 9.95g of liquid 1 was mixed with 12mL of toluene and added to the container. The mixture was heated at 100℃ for 24h. After the reaction was completed, 7.45g of ionone dissolved in 12mL of toluene was added, and the mixture was stirred for another 24h. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0037] This embodiment discloses a method for preparing a hydrophobic additive, including the following steps:
[0038] S1: 6.2 mL of ethyl diazonium acetate was added to a container containing 10 mL of dichloromethane. Under an ice bath at 0 °C, 5.45 mL of pyridine was added. After magnetic stirring for 20 min, 30 mL of dichloromethane containing 27.12 g of heptafluorobutyric anhydride was added. After the addition was complete, the mixture was reacted at room temperature for 10 h. Then, 37.5 mL of distilled water was added, followed by 12 mL of saturated sodium bicarbonate aqueous solution. The reaction was carried out, the mixture was separated, dried, filtered, and purified to obtain organic compound a.
[0039] S2: Under a nitrogen atmosphere, 0.21 mg of copper hydroxide, 40 mg of 4-bromoacetophenone, 126 mg of organic compound a and 94.4 mg of Tempo were added sequentially to a container containing 1.5 mL of tetrahydrofuran, followed by the addition of 92.6 mg of DBU. After reacting at 25 °C for 6 h, organic compound b was obtained.
[0040] S3: Add 78.4 mg of organic compound b to a container containing 5 mL of 10 wt% sodium hydroxide aqueous solution. After oil bath reaction, add 20 wt% sulfuric acid aqueous solution to adjust pH=3, filter, reflux in 37% hydrochloric acid solution for 45 min, rotary evaporate, and vacuum dry to obtain organic compound c.
[0041] S4: Add 3.75g of organic compound c to a container containing 14.5mL of toluene, stir, add 4.05g of dodecanol, then add 0.25g of p-toluenesulfonic acid, heat in an oil bath at 110℃ for 10h, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0042] This embodiment discloses an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 28 parts bisphenol A type epoxy resin, 22 parts modified resin, 24 parts distilled water, 10 parts hydrophobic additive, 16 parts silica, 2 parts sodium tripolyphosphate, 1.5 parts polydimethylsiloxane, and 1.5 parts acrylic leveling agent.
[0043] This embodiment discloses a method for preparing an insulating, anti-corrosion, and anti-condensation coating, comprising the following steps:
[0044] Step 1: Add sodium tripolyphosphate to a container filled with distilled water, stir, then add bisphenol A epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0045] Step 2: Add silica and hydrophobic additives to the mixed base material in sequence, mix evenly, grind, add polydimethylsiloxane and acrylic leveling agent, stir and mix, filter, and cure to obtain an insulating, anti-corrosion and anti-condensation coating.
[0046] Example 2: This example discloses a method for preparing a modified resin, including the following steps:
[0047] Q1: 2.2 g of decamethylcyclopentasiloxane, 18.1 g of 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 0.21 g of 1,1,3,3-tetramethyldisiloxane were added to a container and magnetically stirred for 20 min. Then, 0.004 mL of trifluoromethanesulfonic acid was added. The mixture was heated at 50 °C for 48 h under a nitrogen atmosphere. After the reaction was completed, 0.021 g of hexamethyldisilazane was added and magnetically stirred for 3 h. The mixture was then dried with anhydrous sodium sulfate and stirred for 6 h. After filtration and vacuum distillation, liquid 1 was obtained.
[0048] Q2: 3.12g of perfluorohexyl ethyl acrylate and 0.005mL of platinum catalyst were added to a container containing 20mL of toluene. The mixture was stirred for 2h under a nitrogen atmosphere. Then, 9.22g of liquid 1 was mixed with 12mL of toluene and added to the container. The mixture was heated at 100℃ for 24h. After the reaction was completed, 7.12g of ionone dissolved in 12mL of toluene was added, and the mixture was stirred for another 24h. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0049] This embodiment discloses a method for preparing a hydrophobic additive, including the following steps:
[0050] S1: Add 5.5 mL of ethyl diazonium acetate to a container containing 10 mL of dichloromethane. Under an ice bath at 0 °C, add 5.1 mL of pyridine. After stirring magnetically for 20 min, add 30 mL of dichloromethane containing 26.88 g of heptafluorobutyric anhydride. After the addition is complete, react at room temperature for 10 h. Add 30 mL of distilled water, followed by 12 mL of saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a.
[0051] S2: Under a nitrogen atmosphere, 0.18 mg of copper hydroxide, 35 mg of 4-bromoacetophenone, 123 mg of organic compound a and 92.2 mg of Tempo were added sequentially to a container containing 1 mL of tetrahydrofuran, followed by the addition of 93.8 mg of DBU. After reacting at 25 °C for 6 h, organic compound b was obtained.
[0052] S3: Add 72.6 mg of organic compound b to a container containing 4.5 mL of 10 wt% sodium hydroxide aqueous solution. After oil bath reaction, add 20 wt% sulfuric acid aqueous solution to adjust pH=3. Filter, reflux in 37% hydrochloric acid solution for 45 min, rotary evaporate, and vacuum dry to obtain organic compound c.
[0053] S4: Add 3.42g of organic compound c to a container containing 12.2mL of toluene, stir, add 3.56g of dodecanol, then add 0.22g of p-toluenesulfonic acid, heat in an oil bath at 110℃ for 10h, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0054] This embodiment discloses an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 25 parts bisphenol F type epoxy resin, 26 parts modified resin, 20 parts distilled water, 14 parts hydrophobic additive, 12 parts calcium carbonate, 1 part sodium hexametaphosphate, 1 part white oil, and 2 parts fluorine-modified acrylic leveling agent.
[0055] This embodiment discloses a method for preparing an insulating, anti-corrosion, and anti-condensation coating, comprising the following steps:
[0056] Step 1: Add sodium hexametaphosphate to a container filled with distilled water, stir, then add bisphenol F epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0057] Step 2: Add calcium carbonate and hydrophobic additives to the mixed base material in sequence, mix evenly, grind, add white oil and fluorinated modified acrylic leveling agent, stir and mix, filter, and cure to obtain an insulating, anti-corrosion and anti-condensation coating.
[0058] Example 3: This example discloses a method for preparing a modified resin, including the following steps:
[0059] Q1: 2.7 g of decamethylcyclopentasiloxane, 18.9 g of 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 0.33 g of 1,1,3,3-tetramethyldisiloxane were added to a container and magnetically stirred for 20 min. Then, 0.006 mL of trifluoromethanesulfonic acid was added. The mixture was heated at 50 °C for 48 h under a nitrogen atmosphere. After the reaction was completed, 0.025 g of hexamethyldisilazane was added and magnetically stirred for 3 h. The mixture was then dried with anhydrous sodium sulfate and stirred for 6 h. After filtration and vacuum distillation, liquid 1 was obtained.
[0060] Q2: 3.88g of perfluorohexyl ethyl acrylate and 0.008mL of platinum catalyst were added to a container containing 20mL of toluene. The mixture was stirred for 2h under a nitrogen atmosphere. Then, 10.68g of liquid 1 was mixed with 12mL of toluene and added to the container. The mixture was heated at 100℃ for 24h. After the reaction was completed, 7.78g of ionone dissolved in 12mL of toluene was added, and the mixture was stirred for another 24h. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0061] This embodiment discloses a method for preparing a hydrophobic additive, including the following steps:
[0062] S1: Add 6.8 mL of ethyl diazonium chloride to a container containing 10 mL of dichloromethane. Under an ice bath at 0 °C, add 5.8 mL of pyridine. After stirring magnetically for 20 min, add 30 mL of dichloromethane containing 27.54 g of heptafluorobutyric anhydride. After the addition is complete, react at room temperature for 10 h. Add 45 mL of distilled water, followed by 12 mL of saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a.
[0063] S2: Under a nitrogen atmosphere, 0.23 mg of copper hydroxide, 45 mg of 4-bromoacetophenone, 129 mg of organic compound a and 96.5 mg of Tempo were added sequentially to a container containing 2 mL of tetrahydrofuran, followed by the addition of 91.5 mg of DBU. After reacting at 25 °C for 6 h, organic compound b was obtained.
[0064] S3: Add 84.3 mg of organic compound b to a container containing 5.5 mL of 10 wt% sodium hydroxide aqueous solution. After oil bath reaction, add 20 wt% sulfuric acid aqueous solution to adjust pH=3. Filter, reflux in 37% hydrochloric acid solution for 45 min, rotary evaporate, and vacuum dry to obtain organic compound c.
[0065] S4: Add 4.18g of organic compound c to a container containing 16.8mL of toluene, stir, add 4.54g of dodecanol, then add 0.28g of p-toluenesulfonic acid, heat in an oil bath at 110℃ for 10h, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0066] This embodiment discloses an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 32 parts alicyclic epoxy resin, 18 parts modified resin, 28 parts distilled water, 6 parts hydrophobic additive, 20 parts cellulose, 3 parts sodium polyacrylate, 2 parts monoalkyl phosphate and 1 part polydimethylsiloxane.
[0067] This embodiment discloses a method for preparing an insulating, anti-corrosion, and anti-condensation coating, comprising the following steps:
[0068] Step 1: Add sodium polyacrylate to a container filled with distilled water, stir, then add alicyclic epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0069] Step 2: Add cellulose and hydrophobic additives to the mixed base material in sequence, mix evenly, grind, add monoalkyl phosphate and polydimethylsiloxane, stir and mix, filter, and cure to obtain an insulating, anti-corrosion and anti-condensation coating.
[0070] Example 4: This example discloses a method for preparing a modified resin, including the following steps:
[0071] Q1: 2.3 g of decamethylcyclopentasiloxane, 18.3 g of 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 0.24 g of 1,1,3,3-tetramethyldisiloxane were added to a container and magnetically stirred for 20 min. Then, 0.006 mL of trifluoromethanesulfonic acid was added. The mixture was heated at 50 °C for 48 h under a nitrogen atmosphere. After the reaction was completed, 0.022 g of hexamethyldisilazane was added and magnetically stirred for 3 h. The mixture was then dried with anhydrous sodium sulfate and stirred for 6 h. After filtration and vacuum distillation, liquid 1 was obtained.
[0072] Q2: 3.31g of perfluorohexyl ethyl acrylate and 0.007mL of platinum catalyst were added to a container containing 20mL of toluene. The mixture was stirred for 2h under a nitrogen atmosphere. Then, 9.57g of liquid 1 was mixed with 12mL of toluene and added to the container. The mixture was heated at 100℃ for 24h. After the reaction was completed, 7.25g of ionone dissolved in 12mL of toluene was added, and the mixture was stirred for another 24h. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0073] This embodiment discloses a method for preparing a hydrophobic additive, including the following steps:
[0074] S1: Add 5.8 mL of ethyl diazonium acetate to a container containing 10 mL of dichloromethane. Under an ice bath at 0 °C, add 5.3 mL of pyridine. After stirring magnetically for 20 min, add 30 mL of dichloromethane containing 26.96 g of heptafluorobutyric anhydride. After the addition is complete, react at room temperature for 10 h. Add 32 mL of distilled water, followed by 12 mL of saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a.
[0075] S2: Under a nitrogen atmosphere, 0.19 mg of copper hydroxide, 38 mg of 4-bromoacetophenone, 124 mg of organic compound a and 93.7 mg of Tempo were added sequentially to a container containing 1.8 mL of tetrahydrofuran, followed by the addition of 91.8 mg of DBU. After reacting at 25 °C for 6 h, organic compound b was obtained.
[0076] S3: Add 75.5 mg of organic compound b to a container containing 4.8 mL of 10 wt% sodium hydroxide aqueous solution. After oil bath reaction, add 20 wt% sulfuric acid aqueous solution to adjust pH=3. Filter, reflux in 37% hydrochloric acid solution for 45 min, rotary evaporate, and vacuum dry to obtain organic compound c.
[0077] S4: Add 3.62g of organic compound c to a container containing 13.1mL of toluene, stir, add 3.82g of dodecanol, then add 0.23g of p-toluenesulfonic acid, heat in an oil bath at 110℃ for 10h, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0078] This embodiment discloses an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 26 parts bisphenol A type epoxy resin, 20 parts modified resin, 22 parts distilled water, 8 parts hydrophobic additive, 14 parts barium sulfate, 1.5 parts tripolyphosphate, 1.2 parts white oil, and 1.8 parts acrylic leveling agent.
[0079] This embodiment discloses a method for preparing an insulating, anti-corrosion, and anti-condensation coating, comprising the following steps:
[0080] Step 1: Add tripolyphosphate to a container containing distilled water, stir, then add bisphenol A epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0081] Step 2: Add barium sulfate and hydrophobic additives to the mixed base material in sequence, mix evenly, grind, add white oil and acrylic leveling agent, stir and mix, filter, and cure to obtain an insulating, anti-corrosion and anti-condensation coating.
[0082] Example 5: This example discloses a method for preparing a modified resin, including the following steps:
[0083] Q1: 2.6 g of decamethylcyclopentasiloxane, 18.7 g of 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 0.31 g of 1,1,3,3-tetramethyldisiloxane were added to a container and magnetically stirred for 20 min. Then, 0.004 mL of trifluoromethanesulfonic acid was added. The mixture was heated at 50 °C for 48 h under a nitrogen atmosphere. After the reaction was completed, 0.024 g of hexamethyldisilazane was added and magnetically stirred for 3 h. The mixture was then dried with anhydrous sodium sulfate and stirred for 6 h. After filtration and vacuum distillation, liquid 1 was obtained.
[0084] Q2: 3.71g of perfluorohexyl ethyl acrylate and 0.006mL of platinum catalyst were added to a container containing 20mL of toluene. The mixture was stirred for 2h under a nitrogen atmosphere. Then, 10.28g of liquid 1 was mixed with 12mL of toluene and added to the container. The mixture was heated at 100℃ for 24h. After the reaction was completed, 7.62g of ionone dissolved in 12mL of toluene was added, and the mixture was stirred for another 24h. After the reaction was completed, the mixture was rotary evaporated, washed, and dried to obtain the modified resin.
[0085] This embodiment discloses a method for preparing a hydrophobic additive, including the following steps:
[0086] S1: Add 6.5 mL of ethyl diazonium acetate to a container containing 10 mL of dichloromethane. Under an ice bath at 0 °C, add 5.7 mL of pyridine. After stirring magnetically for 20 min, add 30 mL of dichloromethane containing 27.38 g of heptafluorobutyric anhydride. After the addition is complete, react at room temperature for 10 h. Add 42 mL of distilled water, followed by 12 mL of saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a.
[0087] S2: Under a nitrogen atmosphere, 0.22 mg of copper hydroxide, 42 mg of 4-bromoacetophenone, 128 mg of organic compound a and 95.6 mg of Tempo were added sequentially to a container containing 1.2 mL of tetrahydrofuran, followed by the addition of 93.2 mg of DBU. After reacting at 25 °C for 6 h, organic compound b was obtained.
[0088] S3: Add 82.6 mg of organic compound b to a container containing 5.2 mL of 10 wt% sodium hydroxide aqueous solution. After oil bath reaction, add 20 wt% sulfuric acid aqueous solution to adjust pH=3. Filter, reflux in 37% hydrochloric acid solution for 45 min, rotary evaporate, and vacuum dry to obtain organic compound c.
[0089] S4: Add 4.05g of organic compound c to a container containing 15.2mL of toluene, stir, add 4.21g of dodecanol, then add 0.26g of p-toluenesulfonic acid, heat in an oil bath at 110℃ for 10h, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
[0090] This embodiment discloses an insulating, anti-corrosion, and anti-condensation coating, which is composed of the following components by weight: 31 parts bisphenol F type epoxy resin, 24 parts modified resin, 26 parts distilled water, 12 parts hydrophobic additive, 18 parts silica, 2.5 parts sodium hexametaphosphate, 1.8 parts polydimethylsiloxane, and 1.2 parts acrylic leveling agent.
[0091] This embodiment discloses a method for preparing an insulating, anti-corrosion, and anti-condensation coating, comprising the following steps:
[0092] Step 1: Add sodium hexametaphosphate to a container filled with distilled water, stir, then add bisphenol F epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material;
[0093] Step 2: Add silica and hydrophobic additives to the mixed base material in sequence, mix evenly, grind, add polydimethylsiloxane and acrylic leveling agent, stir and mix, filter, and cure to obtain an insulating, anti-corrosion and anti-condensation coating.
[0094] Comparative Example 1: Compared with Example 1, Comparative Example 1 did not add modified resin during the preparation of the insulating, anti-corrosion and anti-condensation coating, and all other conditions remained unchanged.
[0095] Comparative Example 2: Compared with Example 1, Comparative Example 2 did not add hydrophobic additives during the preparation of the insulating, anti-corrosion and anti-condensation coating, and all other conditions remained unchanged.
[0096] Comparative Example 3: Compared with Example 1, Comparative Example 3 did not add modified resin and hydrophobic additives during the preparation of insulating, anti-corrosion and anti-condensation coating, and all other conditions remained unchanged.
[0097] Performance testing:
[0098] The insulating, anti-corrosion, and anti-condensation coatings prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests. The carbon steel substrate surface was physically cleaned with sandpaper, then wiped with ethanol, and finally rinsed with water. After sandblasting, cleaning, and drying, the samples prepared according to Examples 1-5 and Comparative Examples 1-3 were sprayed using a spray gun. The spraying pressure was 15-20 MPa, the distance between the spray gun and the substrate was 25-35 cm, and the wet film thickness was 150-200 μm. After spraying, the coating was cured at 40-50℃ for 2-4 hours, then heated to 80-100℃ for 4-6 hours. After curing, the coating was allowed to cure for 7 days before performance tests were conducted. Adhesion was tested according to GB / T5210-2006, corrosion resistance according to GB / T 30648.1-2014, and anti-condensation performance according to HG / T 4560-2013. The stain resistance of the samples was tested according to 9780-2013, and the test results are shown in Table 1:
[0099] Table 1
[0100]
[0101] When the pollution level is uncontaminated and the perceived color difference is imperceptible, the stain resistance grade is 0. When the pollution level is very slight and the perceived color difference is barely perceptible, the stain resistance grade is 1. When the pollution level is slight and the perceived color difference is relatively obvious, the stain resistance grade is 2. When the pollution level is moderate and the perceived color difference is very obvious, the stain resistance grade is 3. When the pollution level is severe and the perceived color difference is severe, the stain resistance grade is 4. As shown in Table 1, the test results indicate that by using the methods of Examples 1-5, coatings with excellent adhesion, corrosion resistance, anti-condensation properties, and stain resistance can be prepared. As can be seen from the comparison between Comparative Example 1 and Examples 1-5, the addition of modified resin can effectively improve the adhesion, corrosion resistance, anti-condensation, and stain resistance of the coating; as can be seen from the comparison between Comparative Example 2 and Examples 1-5, the addition of hydrophobic additives can effectively improve the adhesion, corrosion resistance, anti-condensation, and stain resistance of the coating; as can be seen from the comparison between Comparative Example 3 and Examples 1-5, the combined use of modified resin and hydrophobic additives can effectively improve the adhesion, corrosion resistance, anti-condensation, and stain resistance of the coating.
[0102] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0103] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. An insulating, anti-corrosion, and anti-condensation coating, characterized in that, It is composed of the following components by weight: 25-32 parts epoxy resin, 18-26 parts modified resin, 20-28 parts distilled water, 6-14 parts hydrophobic additive, 12-20 parts filler, 1-3 parts dispersant, 1-2 parts defoamer and 1-2 parts leveling agent; The method for preparing the modified resin includes the following steps: Q1: Decamethylcyclopentasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane and 1,1,3,3-tetramethyldisiloxane were added to a container and stirred magnetically. Trifluoromethanesulfonic acid was then added, and the reaction was carried out under a nitrogen atmosphere at a temperature of 50-55°C. After the reaction was completed, hexamethyldisilazine was added, and the mixture was stirred magnetically, dried, stirred, filtered, and distilled under reduced pressure to obtain liquid 1. Q2: Add perfluorohexyl ethyl acrylate and platinum catalyst to a container containing toluene. Stir under a nitrogen atmosphere. Then, mix liquid 1 with toluene and add it to the container. Heat the mixture to react at a temperature of 98-102℃. After the reaction is complete, add ionone dissolved in toluene and continue stirring. After the reaction is complete, rotary evaporate, wash, and dry to obtain the modified resin. The preparation method of the hydrophobic additive includes the following steps: S1: Add ethyl diazonium acetate to a container containing dichloromethane. Under ice bath conditions, add pyridine, stir magnetically, and then add dichloromethane containing heptafluorobutyric anhydride. After the addition is complete, react at room temperature, add distilled water, and then add saturated sodium bicarbonate aqueous solution. React, separate the contents, dry, filter, and purify to obtain organic compound a. S2: Under a nitrogen atmosphere, copper hydroxide, 4-bromoacetophenone, organic compound a and 2,2,6,6-tetramethylpiperidine-1-oxy radical Tempo were added sequentially to a container containing tetrahydrofuran, followed by the addition of 1,8-diazabicyclo[5.4.0]undec-7-ene DBU. After sealing the reaction, organic compound b was obtained. S3: Add organic compound b to a container containing sodium hydroxide aqueous solution, react in an oil bath, add sulfuric acid aqueous solution, adjust pH to 3-3.2, filter, reflux, rotary evaporate, and vacuum dry to obtain organic compound c; S4: Add organic compound c to a container containing toluene, stir, add dodecanol, then add p-toluenesulfonic acid, heat in an oil bath at 110-130℃, after the reaction is complete, wash, dry, and purify to obtain the hydrophobic auxiliary agent.
2. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In Q1, the ratio of decamethylcyclopentasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, 1,1,3,3-tetramethyldisiloxane, trifluoromethanesulfonic acid, and hexamethyldisilazane is (2.2-2.7) g : (18.1-18.9) g : (0.21-0.33) g : (0.004-0.006) mL : (0.021-0.025) g.
3. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In Q2, the ratio of perfluorohexyl ethyl acrylate, platinum catalyst, liquid 1 and ionone is (3.12-3.88) g : (0.005-0.008) mL : (9.22-10.68) g : (7.12-7.78) g.
4. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In S1, the ratio of ethyl diazoate, pyridine, heptafluorobutyric anhydride and distilled water is (5.5-6.8) mL : (5.1-5.8) mL : (26.88-27.54) g : (30-45) mL.
5. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In S2, the ratio of copper hydroxide, 4-bromoacetophenone, organic compound a, Tempo, tetrahydrofuran, and DBU is (0.18-0.23) mg: (35-45) mg: (123-129) mg: (92.2-96.5) mg: (1-2) mL: (91.5-93.8) mg.
6. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In S3, the ratio of organic compound b to sodium hydroxide aqueous solution is (72.6-84.3) mg: (4.5-5.5) mL.
7. The insulating, anti-corrosion, and anti-condensation coating according to claim 1, characterized in that, In S4, the ratio of organic compound c, toluene, dodecyl alcohol and p-toluenesulfonic acid is (3.42-4.18) g : (12.2-16.8) mL : (3.56-4.54) g : (0.22-0.28) g.
8. A method for preparing an insulating, anti-corrosion, and anti-condensation coating as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Add the dispersant to a container filled with distilled water, stir, then add epoxy resin and modified resin, continue stirring to react, and obtain a mixed base material; Step 2: Add the filler and hydrophobic additive to the mixed base material in sequence, mix evenly, grind, add defoamer and leveling agent, stir and mix, filter, and mature to obtain an insulating, anti-corrosion and anti-condensation coating.
Citation Information
Patent Citations
Anti-condensation coating for high-voltage switch cabinet as well as preparation method and application of anti-condensation coating
CN114591670A
Nano anti-condensation transparent insulating paint suitable for power grid and preparation method of nano anti-condensation transparent insulating paint
CN118165592A
